Early increase of carotid intima-media thickness in children with parental history of premature myocardial infarction. Issue 8 (23rd January 2009) - Barra, S; Gaeta, G; Cuomo, S; Guarini, P; Foglia, M C; Capozzi, G; Materazzi, C; Trevisan, M
Abstract : Background/objective: Increased carotid intima-media thickness (IMT) is an early manifestation of atherosclerosis. Our group has previously demonstrated that a parental history of premature myocardial infarction (PHPMI) is associated with an increase in carotid IMT in children-adolescents (mean age 13 years) and young adults (mean age 24 years). The aim of the present study was to evaluate if carotid structural changes are detectable in young children with PHPMI. Methods: 26 healthy children (9 males and 17 females; 5–12 years, mean age 9.1 (2.5) years) with PHPMI and 26 age-matched (plus or minus 1 year), sex-matched and body mass index-matched (BMI; plus or minus 20%) control subjects were enrolled in the study. They underwent high resolution B-mode ultrasonographic evaluation of common carotid artery IMT. Lipid profile, resting blood pressure and BMI were also evaluated. Results: Compared to controls, subjects with PHPMI had increased IMT of common carotid arteries (mean of combined sites: 0.444 (0.076) mm versus 0.382 (0.062) mm in controls, p = 0.001). Offspring of coronary patients showed an unfavourable lipid profile compared to controls; however, the association between a PHPMI and carotid IMT was independent of lipids, apolipoproteins and other traditional risk factors. Conclusions: Vascular structural changes are detectable in subjects with PHPMI at a young age and occur independently of several traditional cardiovascular risk factors.